In the backlight: Augustus in Plutarch - Pinto, Ana Paula (2021)
True synthesis of the richest classical tradition between Greek essence and Roman naturalness, Plutarch's work will always show a structural tendency to reconciliation of two changeable worlds. Although cited in the Lamprias's Catalog, the Αὐγούστου Βίος has not survived, and readers only know an indirect portrait of Augustus, in the shade of other historical figures like his predecessor Iulius Caesar, the adversary Antony, or the emulus Alexander. From this diffuse portrait it is however possible to capture the emperor's image and the influence he could exert on the conscience of a colonized.